The Effect of Firm Size, Profitability, and Liquidity on The Firm Value Moderated by Carbon Emission Disclosure - Dody Hapsoro; Zaki Naufal Falih (Journal of Accounting and Investment, 2020)
Research aims: The purpose of this study is to examine carbon emission disclosure in moderating the effect of firm size, profitability, and liquidity on the firm value.Design/Methodology/Approach: The sample used in this study was firms engaged in the oil, gas, and coal fields and operating in non-Annex 1 member countries registered in the Osiris database. The study period was following the commencement of the Kyoto Protocol's second commitment from 2015 to 2018. Data analysis in this study used Partial Least Square (PLS) with Warp PLS 4.0 application.Research findings: The study results showed that firm size and liquidity had a positive and significant effect on firm value. However, profitability had a positive and insignificant effect on firm value. Besides, carbon emission disclosure moderated the effect of firm size and profitability on firm value. However, carbon emission disclosure did not moderate the effect of liquidity on firm value.Theoretical contribution/ Originality: This study provides insight that carbon emission disclosure can moderate the effect of firm size and profitability variables on firm value.Practitioner/Policy implication: This study is expected to encourage firms to be more concerned about the environment. Furthermore, the political contribution that can be provided by the results of this study is expected to motivate the government to apply more stringent regulations to firms that have the potential to generate carbon emissions.Research limitation/Implication: Limitation in this study is the amount of data from oil firms, gas, and coal contained in the Osiris database in 2015 until 2018 was very limited.